Internalizing and Externalizing Disorders as Predictors of Alcohol Use Disorder Onset during Three Developmental Periods - Farmer, Richard F. (Drug Alcohol Depend, 2016)
BACKGROUND: The developmental pathways associated with an enhanced risk for future alcohol use disorders (AUDs) continue to be a topic of both interest and debate. In this research, internalizing and externalizing disorders were evaluated as prospective predictors of the index AUD episode onset, separately within three developmental periods: early-to-middle adolescence (age 13.0 to 17.9), late adolescence (18.0 to 20.9), and early adulthood (21.0 to 30.0). METHODS: Participants (N = 816) were initially randomly selected from nine high schools in western Oregon and subsequently interviewed on four separate occasions between ages 16 and 30, during which current and past AUDs were assessed as well as a full range of psychiatric disorders associated with internalizing and externalizing psychopathology domains. RESULTS: In adjusted analyses for each of the three developmental periods investigated, externalizing domain psychopathology from the most proximal adjoining developmental period predicted time to AUD onset. Distal externalizing psychopathology also predicted time to AUD onset among early adult onset cases. Proximal or distal internalizing psychopathology, in comparison, was not found to be a significant predictor of AUD onset in adjusted analyses for any of the developmental periods examined. CONCLUSIONS: Findings overall suggest that externalizing developmental histories are robust predictors of AUD onset within the age range during which index episodes are most likely to occur, and that gender does not moderate this association.